Knowledge, attitudes, and practices towards artificial intelligence among young pediatricians: A nationwide survey in France - Perrier, Emma; Rifai, Mahmoud; Terzic, Arnaud; Dubois, Constance; Cohen, Jérémie F. (Frontiers in Pediatrics, 2022)
Objective: To assess the knowledge, attitudes, and practices (KAP) towards artificial intelligence (AI) among young pediatricians in France. Methods: We invited young French pediatricians to participate in an online survey. Invitees were identified through various email listings and social media. We conducted a descriptive analysis and explored whether survey responses varied according to respondents' previous training in AI. Results: In total, 165 French pediatricians participated in the study (median age 27 years, women 78%, residents 64%). While 90% of participants declared they understood the term “artificial intelligence”, only 40% understood the term “deep learning". Most participants expected AI would lead to improvements in healthcare (e.g., better access to healthcare, 80%; diagnostic assistance, 71%), and 86% declared they would favor implementing AI tools in pediatrics. Fifty-nine percent of respondents declared seeing AI as a threat to medical data security and 35% as a threat to the ethical and human dimensions of medicine. Thirty-nine percent of respondents feared losing clinical skills because of AI, and 6% feared losing their job because of AI. Only 5% of respondents had received specific training in AI, while 87% considered implementing such programs would be necessary. Respondents who received training in AI had significantly better knowledge and a higher probability of having encountered AI tools in their medical practice (p <0.05 for both). Conclusion: In this survey, most young French pediatricians had favorable views toward AI, but a large proportion expressed concerns regarding the ethical, societal, and professional issues linked with the implementation of AI.